Modeling technology transfer for petroleum industry in Libya: an overview - Mohamed, Al Mabruk S.; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Hamouda, Abdel Magid Salem; Baharudin, B. T. Hang Tuah (Academic Journals, 2010)
The purpose of this study was to review and criticize the accessible literature of technology transfer (TT). To reduce the literature to convenient proportions, the focus would be on literature on modeling of technology transfer in the diverse industry sectors. The foremost purpose of the paper was to put forward an appropriate conceptual TT model in the context of Libyan oil industry. Uncertainly, foreign companies operating in Libyan petroleum industry may possibly transfer technology provided certain conditions. However, imported petroleum technology might not essentially be transferred flawlessly. The paper begins by examining the factors accommodated in each model believed to influence the TT process effectiveness. Based on our review, the conceptual model derived to include key factors of TT to evaluate TT performance, and examine interrelations between TT government support, TT infrastructure, TT environment, and TT learning capability.